Refleksje nad kryzysami własnej tożsamości - Zenomena Płużek (Jesuit University Ignatianum in Krakow, 2017)
It seems justified to affirm that man cannot know himself completely. This truth has a great influence on considering and comprehending his identity. Although people used to think that identity is based on the intellectual perception of one's own personality, an equally essential factor appears the element of volition. It has to be emphasised that man constitutes the highest value for himself and for other people, for whom he should be responsible. In this sphere, human identity crises arise. Talking about crises, then, one should look for the causes in the mistaken Refleksje nad kryzysami własnej tożsamości hierarchy of values and, finally, in the question: who am I? The crises, however, do not have to be entirely negative and that is why the author presumes the necessity of empirical investigation into their origins.